Book review: Peregruznoe I Burial Ground: Results of Interdisciplinary Research : Monograph [Text] / M. A. Balabanova, E. V. Pererva [at al.]. – Volgograd : Izd-vo Volgogradskogo Filiala FGBOU VPO RANHiGS, 2014. – 360 p. - Tairov Aleksandr Dmitrievich (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2016)
The review concerns the monograph “Peregruznoe I Burial Ground: Results of Interdisciplinary Research. The book was prepared by the team of authors including archaeologists, anthropologists, paleosoil specialists, archaeozoologists. The review contains examination of materials and main conclusions for every chapter of the monograph. The monograph is devoted to the analysis of materials from 52 burial mounds dated from the Aeneolith to the Middle Ages. Most of them were erected in the Sarmatian period.